Efficacy of Socket-Shield Technique on Tissue Stability of Immediate Implant Placement: A Systematic Review with Meta-Analysis and Trial Sequential Analysis - Reza Birang; Jaber Yaghini; Shirin Zahra Farhad; Mahsa Ahmadi Shadmehri; Zohreh Afshari; Pedram Iranmanesh; Mohammad Reza Maracy; Amir Khorasani Zadeh (Wolters Kluwer Medknow Publications, 2022)
Objective: To compare the socket-shield technique (SST) with the conventional method of immediate implant placement (IIP) regarding stabilization of buccal hard and soft tissue, and esthetic management. Method and Materials: Randomized controlled trials (RCT) investigating SST, published in English, were searched in MEDLINE/PubMed, Web of Science, Scopus, Cochrane, ProQuest, OpenGrey, and Embase until May May 2021, in June 2021. The quality assessment of included RCTs was conducted using the Cochrane Collaboration's tools. A STATA version 16 was used to determine mean difference with 95% confidence intervals for buccal plate width (BPW), buccal plate height (BPH), pink esthetic score (PES), and implant stability quotient for 3, 6, and 12 months follow-up subgroups. Results: Out of 4617 records, 10 RCTs were finally included for the review and meta-analysis. Regarding BPW, significant differences were observed in favor of SST after 6 months. Also significant difference was detected in BPH and PES in favor of SST compared to the conventional method for all time points. However, no significant difference was found regarding implant stability between the two groups. Conclusion: SST yields better outcomes in dimensional changes of bone and soft tissue, and is found to be superior to conventional IIP regarding esthetic results and stability of hard and soft tissue around implants.